2022
DOI: 10.1002/pds.5548
|View full text |Cite
|
Sign up to set email alerts
|

Methods for drug safety signal detection using routinely collected observational electronic health care data: A systematic review

Abstract: Purpose: Signal detection is a crucial step in the discovery of post-marketing adverse drug reactions. There is a growing interest in using routinely collected data to complement established spontaneous report analyses. This work aims to systematically review the methods for drug safety signal detection using routinely collected healthcare data and their performance, both in general and for specific types of drugs and outcomes.Methods: We conducted a systematic review following the PRISMA guidelines, and regis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 143 publications
0
9
0
Order By: Relevance
“…Furthermore, they highlighted that only one of their included studies investigated the timeliness of signal detection. 7 Therefore, we investigated which of the papers included in the review by Coste et al analysed their data at multiple time points as the authors did not focus on this aspect. Additionally, on 3 March 2023, we updated the systematic search conducted by Coste et al to include papers available after 13 July 2021.…”
Section: Safety Signal Detection In Electronic Healthcare Datamentioning
confidence: 99%
See 4 more Smart Citations
“…Furthermore, they highlighted that only one of their included studies investigated the timeliness of signal detection. 7 Therefore, we investigated which of the papers included in the review by Coste et al analysed their data at multiple time points as the authors did not focus on this aspect. Additionally, on 3 March 2023, we updated the systematic search conducted by Coste et al to include papers available after 13 July 2021.…”
Section: Safety Signal Detection In Electronic Healthcare Datamentioning
confidence: 99%
“…3 Recently, the list of methods for signal detection in electronic healthcare data was updated by Coste et al They further compared the performance of the methods overall and for specific types of exposures and outcomes. 7 The authors concluded that no method was superior for all drugs and outcomes and propose that more than one method may be applied for signal detection among multiple drug-outcome pairs. Furthermore, they highlighted that only one of their included studies investigated the timeliness of signal detection.…”
Section: Safety Signal Detection In Electronic Healthcare Datamentioning
confidence: 99%
See 3 more Smart Citations